Climate change allowances, non‐stationarity and flood frequency analyses. Issue 3 (11th January 2022) - Griffin, Adam; Kay, Alison; Stewart, Lisa; Spencer, Peter
Abstract: When considering future adaptation to climate change in UK fluvial flood alleviation schemes, the current recommendation by the Environment Agency (England) is to increase peak design flood flows by a preselected percentage. This allowance varies depending on the period for which the estimate is being made, the vulnerability of the development being considered and its location. Recently, questions have been raised as to whether these percentage uplifts should be kept the same, or whether change has already happened within the baseline period and so uplifts should be reduced. A complicating factor is that changes in flood frequency can occur for reasons in addition to climate change, such as land‐use change or natural variability. This article describes current approaches taken by different stakeholders for catchments in England and Wales to account for climate change, and discusses these allowances where there is already an observed presence of trend in flood regimes. Theil–Sen estimators of trend were used in comparing non‐stationary and stationary flood frequency curves with allowances applied, leading to a recommendation of evaluating non‐stationary models at 1990, the end of the reference period. Examples were explored such as the Eden catchment, which was heavily affected by Storm Desmond in December 2015.